Investigation of calcium zirconate formation by sintering zirconium dioxide with calcium hydroxide. Issue 10 (July 2018) - Jahn, Constantin; Schafföner, Stefan; Ode, Christian; Jansen, Helge; Aneziris, Christos G.
Abstract: The present paper analysed the formation of calcium zirconate from zirconium dioxide and calcium hydroxide through solid state reaction. Different mole ratios and sintering temperatures are investigated. The sintering temperature was reduced to 1200 °C. Due to the decomposition process of the calcia source during firing the volume expansion in the sintered samples was remarkable. A good homogenisation of the raw mixture is necessary to obtain a complete reaction of the material. The microstructure of the calcium zirconate gained from calcium hydroxide and from calcium carbonate did not differ. Moreover, a difference in reactivity due to varying microstructure and temperature of decomposition between the different calcia sources could not be determined. Thus calcium carbonate is less hazardous and resulted in a higher yield of calcium zirconate compared to calcium hydroxide as calcia source.